THE INFLUENCE OF SERVICE QUALITY AND CUSTOMERS’ VALUE ON CUSTOMERS’ SATISFACTION AND THE IMPACT ON CUSTOMERS’ LOYALTY AT GRAPARI TELKOMSEL TSM BANDUNG - Adi Suparwo; Suryana Suryana; Alfin Zulkifli (Universitas Pasundan, 2022)
This study aims to determine how much influence service quality and customers’ value have on customer satisfaction and to determine customer loyalty at GraPARI Telkomsel TSM Bandung. The research method used is descriptive and verification method, where data is collected through observation, interviews, and distributing questionnaires with a total sample of 97 respondents. The research testing instrument uses validity and reliability tests. The data analysis method used is path analysis, multiple correlation, and coefficient of determination. The results showed that there was a positive and significant influence between quality and customers’ value on customers’ satisfaction and increasing customers’ loyalty either simultaneously or partially. Based on the findings in the study that companies that provide the best service quality will make an assessment that the services provided provide satisfaction and customers will be loyal by themselves to the company. There is a difference between this study and previous research, namely that there are no previous researchers who specifically discussed marketing strategies through customer value at GraPARI Telkomsel customer service centers, especially at GraPARI Telkomsel TSM Bandung.